Improving the dependability of dynamically reconfigurable hardware by concurrent replication of active resources - José M. M. Ferreira (2005)
This presentation describes a low-level technique to replicate active resources (i.e. resources that are being used by functions that are currently running) in dynamically reconfigurable FPGAs, with the main objective of releasing them to be tested in a non-intrusive way. This technique may be used to support i) Online concurrent testing to detect any faults that emerge during system operation, ii) Enhanced fault tolerance (restoring the reliability index by replacing a defective resource), and iii) Reallocation of the FPGA logic space to prevent excessive delays or wasting resources due to fragmentation. All solutions proposed reuse the IEEE 1149.1 (JTAG) test access port and boundary-scan architecture to ensure a low-cost / low overhead implementation.